Analysis of The Implementation program Numeracy Literacy for Teacher Working Groups in Building a Literate Culture - Humairah, Humairah; Khasanah, Linaria Arofatul Ilmi Uswatun; Riansyah, Daffa Maulana (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2024)
This study aims to describe the analysis of the implementation programe numeracy literacy in teachers' working groups to build a culture of literacy in primary schools. This research used a qualitative method with a descriptive approach. The research subjects were six teachers who had attended literacy and numeracy training at MIM 16 Payaman and MIM 05 Palirangan. Data collection techniques were conducted using interviews, observation, and documentation. The results showed that the literacy and numeracy program in the teachers' working group can apply tactical implementation strategies to literacy and numeracy skills in the physical, socio-emotional, and academic domains so this is the starting point for creating a culture of literacy in schools. Teachers can also carry out mapping, advocacy, mentoring, monitoring, and evaluation of literacy and numeracy activities carried out at school. Teachers can carry out various activities to implement a culture of numeracy literacy at school and home, such as creating a reading corner in the classroom. Teachers can integrate literacy and numeracy skills through tasks carried out by students according to what is obtained from the teacher's working group.